Protocol for predicting the single-cell network-based gene activity landscape during human B cell development - Xin Huang; Xuetong Hou; Yizhen Li; Jun J. Yang; Jiyang Yu (STAR Protocols)
Summary: Owing to inconsistencies in human B cell classification and the difficulty in distinguishing heterogeneous subpopulations, we present a protocol to construct gene regulatory networks and gene activity landscapes for human B cell developmental stages. We describe steps for acquiring bone marrow data; conducting single-cell downstream analysis; and leveraging the St. Jude Algorithm for the Reconstruction of Accurate Cellular Networks (SJARACNe), Network-based Bayesian Inference of Drivers (NetBID2), and single-cell Mutual Information-based Network Engineering Ranger (scMINER) algorithms for network-based analysis. Our protocol elucidates the biological characteristics of developmental stages in human B cells.For complete details on the use and execution of this protocol, please refer to Huang et al.1 : Publisher’s note: Undertaking any experimental protocol requires adherence to local institutional guidelines for laboratory safety and ethics.